2007
DOI: 10.1091/mbc.e07-03-0196
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Coupled Biogenesis of Yeast Gap1 Permease and Sphingolipids: Essential Role in Transport Activity and Normal Control by Ubiquitination

Abstract: Current models for plasma membrane organization integrate the emerging concepts that membrane proteins tightly associate with surrounding lipids and that biogenesis of surface proteins and lipids may be coupled. We show here that the yeast general amino acid permease Gap1 synthesized in the absence of sphingolipid (SL) biosynthesis is delivered to the cell surface but undergoes rapid and unregulated down-regulation. Furthermore, the permease produced under these conditions but blocked at the cell surface is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 72 publications
(131 reference statements)
5
67
0
Order By: Relevance
“…As described below, several other integral proteins localize to MCC. A number of other plasma membrane proteins, such as hexose trasporter Hxt1 or general amino acid permease Gap1, distribute homogeneously in the membrane [13,17]. Finally, it has been shown that the predominant yeast plasma membrane protein H + -ATPase, Pma1, strictly avoids MCC patches and resides in the area in between them ( Figure 1C).…”
Section: Plasma Membrane Domains In Yeastmentioning
confidence: 95%
See 1 more Smart Citation
“…As described below, several other integral proteins localize to MCC. A number of other plasma membrane proteins, such as hexose trasporter Hxt1 or general amino acid permease Gap1, distribute homogeneously in the membrane [13,17]. Finally, it has been shown that the predominant yeast plasma membrane protein H + -ATPase, Pma1, strictly avoids MCC patches and resides in the area in between them ( Figure 1C).…”
Section: Plasma Membrane Domains In Yeastmentioning
confidence: 95%
“…Specific lipid requirements were also reported for other plasma membrane proteins. The plasma membrane targeting of Gap1 (normally homogeneously distributed) and of Pma1 (MCP-resident) is impaired in cells defective in long-acyl chains biosynthesis [6,13]. Long chain bases also regulate the phosphorylation of the primary components of the eisosome, Pil1 (phosphorylation inhibited by long chain bases) and Lsp1 (long chain bases stimulate phosphorylation).…”
Section: Role Of Lipidsmentioning
confidence: 99%
“…Another plasma membrane protein, the general amino acid permease Gap1, depends in various ways upon sphingolipids (102). Gap1 synthesized in lcb1-100 cells at a restrictive temperature is transported to the plasma membrane but is not incorporated into detergent-resistant lipid rafts, lacks amino acid transport activity, and is rapidly endocytosed in a ubiquitin-mediated manner.…”
Section: Yeast Sphingolipidsmentioning
confidence: 99%
“…Permease misfolding has also been illustrated in the case of the Gap1 permease synthesized under conditions inhibiting sphingolipid biogenesis, and this causes its Ub-dependent downregulation (12). Inhibition by rapamycin of TORC1, as well as various stress conditions likely reducing TORC1 activity, also promotes Gap1 downregulation.…”
mentioning
confidence: 99%